Speaker Verification Using Hybrid Scheme for Arabic Speech - Moharom ed, H.R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work , a hybrid scheme tor Arabic speech for the recognition of the speaker verification is presented . The scheme is hybrid as utilizes the traditional digi tal signal processi ng and neural network . Kohonen neural network has been used as a recognizer tor speaker verification after extract spectral features from an acoustic signal by Fast Fourier Transformation Algorithm(FFT) . The system was im plemented using a PENTIUM processor , I000 MHZ compatible and MS-dos 6.2 .